Spinal Cord Stimulation: The Clinical Application of New Technology - Dominic Hegarty (Anesthesiology Research and Practice)
The use of neuromodulation for pain relief is among the fastest-growing areas of medicine, involving many diverse specialties and impacting on hundreds of thousands of patients with numerous disorders worldwide. As the evidence of efficacy improves, the interest in spinal cord stimulation (SCS) will increase because it is minimally invasive, safe, and a reversible treatment modality with limited side effect profile. While the mechanism of action evades complete understanding, the technological improvements have been considerable and current neuromodulation developments have been coupled with the rapid growth of the neuromodulation device industry resulting in the development of the next-generation neuromodulation systems. The development, the newest technicaliti and the future for the clinical application of spinal cord stimulation (SCS) are reviewed here.